2018
DOI: 10.1080/1068316x.2018.1538417
|View full text |Cite
|
Sign up to set email alerts
|

From devil’s advocate to crime fighter: confirmation bias and debiasing techniques in prosecutorial decision-making

Abstract: This research examines the role of confirmation bias in prosecutorial decisions before, during and after the prosecution. It also evaluates whether confirmation bias is reduced by changing the decision maker between arrest and prosecution. In Experiment 1, Swedish prosecutors (N = 40) assessed 8 scenarios where they either decided themselves or were informed about a colleague's decision to arrest or not arrest a suspect. Participants then rated how trustworthy the suspect's statement was as well as the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Interventions can range from fast and frugal options to intensive training sessions (Sellier et al, 2019 ). Information managers and decision-makers can be trained to counter-check their assumptions by actively seeking disconfirming information and considering the opposite of their preliminary hypothesis (Satya-Murti and Lockhart, 2015 ; Lidén et al, 2019 ). Future research needs to test the effectiveness of such interventions in crisis settings.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions can range from fast and frugal options to intensive training sessions (Sellier et al, 2019 ). Information managers and decision-makers can be trained to counter-check their assumptions by actively seeking disconfirming information and considering the opposite of their preliminary hypothesis (Satya-Murti and Lockhart, 2015 ; Lidén et al, 2019 ). Future research needs to test the effectiveness of such interventions in crisis settings.…”
Section: Discussionmentioning
confidence: 99%
“…Research involving actual interrogators found similar effects. When police officers formulated questions for suspects described in vignettes, they opted to use more guilt-presumptive questions after learning that a suspect had been apprehended (Lidén, Gräns, & Juslin, 2019).…”
Section: Stage 1: Precustodial Interviewmentioning
confidence: 99%
“…Only a handful are experimental studies (e.g. Darwinkel et al, 2015;Lidén et al, 2019;Pezdek & O'Brien, 2014). Most of these studies investigate the influences of various case characteristics in sexual assault cases.…”
Section: Discussionmentioning
confidence: 99%
“…Netherlands imply that judges often try to corroborate the prosecutors' decisions by actively looking for confirming evidence (Tersago et al, 2020) or that judges focus on excluding alternative scenarios rather than finding the scenario that best explains the evidence (Maegherman, 2021). Also, Swedish prosecutors displayed a guilt-confirming mindset once they have charged a suspect (Lidén et al, 2019). Since the structure of the law of criminal procedure triggers psychological mechanisms in prosecutors and judges, thereby shaping the decisions of both, the initial preference for the incriminating story may not be compensated for in the trial (e.g.…”
mentioning
confidence: 99%